An Analysis of Teacher’s Strategies in Teaching English Speaking at Vocational High School - Nisak, Karimatun; Masruroh, Lailatul (IKIP Siliwangi, 2025)
This study aims to analyze the strategies employed by an English teacher in teaching speaking to eleventh-grade students at SMK Assa’adah Bungah Gresik and to describe the students’ responses toward those strategies. Using a descriptive qualitative method, data were collected through classroom observations, student questionnaires, and documentation. The findings reveal that the teacher applied various strategies such as group discussions, storytelling, drilling, simulations, oral presentations, and communication games to support speaking skill development. Among these, group discussions and communication games were the most frequently used, while simulations and storytelling appeared less often. Students responded positively to interactive activities that encouraged participation and made learning enjoyable. They reported improved confidence, fluency, and motivation when engaged in group-based or game-like speaking tasks. Documentation, including photos and lesson materials, confirmed the application of these strategies in classroom practice. The study concludes that communicative and student-centered approaches are effective in enhancing students’ speaking abilities when applied consistently and contextually. These results suggest that incorporating a variety of engaging speaking strategies can support English language development in vocational high school.